2017
DOI: 10.18332/tpc/67799
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of short term use of e-cigarettes on airways physiology and respiratory symptoms in smokers with and without airways obstructive diseases and in healthy non smokers

Abstract: BACKGROUND Although the use of e-cigarettes is increasing worldwide, their short and long-term effects remain undefined. We aimed to study the acute effect of short-term use of e-cigarettes containing nicotine on lung function and respiratory symptoms in smokers with airways obstructive disease (COPD, asthma), "healthy" smokers, and healthy never smokers. METHODS Respiratory symptoms, vital signs, exhaled NO, airway temperature, airway resistance (Raw), specific airway conductance (sGaw) and single nitrogen br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 42 publications
2
45
0
2
Order By: Relevance
“…The MA, however, expressed this pattern more prominently, as they exhibited a significantly higher degree of changes for Z5, R5 and R10 than the HS and a significant decrease in X5 that was insignificant in the HS. These results complement previous findings that showed increased airway resistance (Raw) in HS and asthmatic smokers …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The MA, however, expressed this pattern more prominently, as they exhibited a significantly higher degree of changes for Z5, R5 and R10 than the HS and a significant decrease in X5 that was insignificant in the HS. These results complement previous findings that showed increased airway resistance (Raw) in HS and asthmatic smokers …”
Section: Discussionsupporting
confidence: 92%
“…E‐cigarette smoking (ECS) has been shown to be associated with respiratory symptoms, immediate pulmonary dysfunction and oxidative stress expressed as increased flow resistance and reduced fractional exhaled nitrogen oxide (FeNO) . However, the time course of such alterations has not been previously examined and the duration of the immediate pulmonary effects of ECS is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A human study (30 smokers versus controls) showed that acute inhalation of ECIG vapour increased respiratory impedance and airway resistance, but did not immediately impact forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) ratio [100]. Another study showed an acute effect of ECIGs on airway resistance, showing increasing of airway resistance in asthmatic smokers, healthy smokers and never-smokers (ECIGs with and without nicotine) [101]. A separate study with 15 smokers and 15 controls found no effect of acute ECIG exposure on lung function as determined by FEV1/FVC ratio [102].…”
Section: Health Effectsmentioning
confidence: 99%
“…Health effect studies are difficult to design because most ECIG users are either past or current cigarette smokers. Short-term, experimental use of ECIGs has been shown to have acute effects on airways physiology and respiratory symptoms in COPD smokers, asthmatic smokers, "healthy" smokers and healthy never-smokers [101]. Common adverse effects include throat irritation and cough [182].…”
Section: Human Health Effectsmentioning
confidence: 99%